The role of penal mediation In achieving restorative justice - Feirouz El Maouhab (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
Despite all the efforts made by the state as it has the right to impose punishment and fight crime, the phenomenon of crime is constantly increasing, in addition to the increase and accumulation of cases related to it before the penal judicial authorities, which has led to the emergence of a stifling crisis known as “the criminal justice crisis” due to excessive asylum to criminalization and focus on punitive policy, which called for searching for alternatives to public action as a means of rationalizing criminal policy and moving towards a new concept of justice from punitive deterrent justice to consensual restorative justice to resolve disputes.